Através do espelho: e o que a igualdade política encontrou por lá - João Henrique Alves Meira (2017)
The purpose of this study was to explore in a detained way the distribution of political power in democratic societies and its impact on law. Assuming that political equality is a discussion about the distribution of political power in a democracy, the Direct Unconstitutionality Action (ADIN) 4.650 was chosen to analyze the position of the Federal Supreme Court in relation to political equality. From this analysis, general lines were drawn by reading each of the votes, in order to obtain more knowledge about the political philosophy bases upon which the judges' arguments were constructed. It was possible to notice that the reasoning drawn by the judges withdraws its basis, to a large extent, from liberal political-philosophical theories. Through this hypothesis, this work brought a general perspective on political liberalism, offering a more detailed explanation on egalitarian liberalism, especially on John Rawls's theory of justice and the impact of this theory on the understanding of political equality in Brazil. From these general lines of liberalism some criticisms of liberal thought have been put forward, which point to the inability of liberalism to deal with current democratic crises, which in turn has exposed the need to investigate other political-philosophical views. As alternative references to liberal thought Chantal Mouffe's theory of agonist politics and Michael Walzer's theory of justice were chosen. Through the exposition of the two theories was woven a notion of politics necessarily conflictual, diverse and specific to each political community, before which individual and collective identities are created and developed; and equality as the protection of the meaning of social goods. From this new perception were established the possible legal implications in the use of this notion of political equality in the Brazilian context. Finally, final considerations on the relationship between the current crisis of democracy and liberal logic were presented, exposing the Mouffian and Walzerian potentialities in seeking a substantive political-philosophical content. From this point of view, the formation of the subject, not from the pure reason, but from a complex system of relations between the individual and the surrounding environment, allows a more reasonable view of human capacities. Thus, the subject and its objectives would be composed of a process of historical-cultural construction, in the same way as the social goods used by the subjects. The Truth becomes constituted by several truths, being perceived as definitions affirmed politically and that look to the horizon of democracy-pluralist believing in the same as the best form of political organization.